A packaged intervention to improve viral load monitoring within a deeply rural health district of South Africa - Brijkumar, J. (BMC Infect Dis, 2020)
BACKGROUND: The KwaZulu-Natal (KZN) province of South Africa has the highest prevalence of HIV infection in the world. Viral load (VL) testing is a crucial tool for clinical and programmatic monitoring. Within uMkhanyakude district, VL suppression rates were 91% among patients with VL data; however, VL performance rates averaged only 38·7%. The objective of this study was to determine if enhanced clinic processes and community outreach could improve VL monitoring within this district. METHODS: A packaged intervention was implemented at three rural clinics in the setting of the KZN HIV AIDS Drug Resistance Surveillance Study. This included file hygiene, outreach, a VL register and documentation revisions. Chart audits were used to assess fidelity. Outcome measures included percentage VL performed and suppressed. Each rural clinic was matched with a peri-urban clinic for comparison before and after the start of each phase of the intervention. Monthly sample proportions were modelled using quasi-likelihood regression methods for over-dispersed binomial data. RESULTS: Mkuze and Jozini clinics increased VL performance overall from 33·9% and 35·3% to 75·8% and 72·4%, respectively which was significantly greater than the increases in the comparison clinics (RR 1·86 and 1·68, p < 0·01). VL suppression rates similarly increased overall by 39·3% and 36·2% (RR 1·84 and 1·70, p < 0·01). The Chart Intervention phase showed significant increases in fidelity 16 months after implementation. CONCLUSIONS: The packaged intervention improved VL performance and suppression rates overall but was significant in Mkuze and Jozini. Larger sustained efforts will be needed to have a similar impact throughout the province.